Daylight-mediated photodynamic therapy for actinic damage in Latin America: consensus recommendations (2016)
ABSTRACT: Although conventional photodynamic therapy (c-PDT) using methyl aminolevulinate cream (MAL) is effective for the treatment of grade I-II facial and scalp actinic keratosis (AK), it is associated with treatmentrelated pain for some patients. Daylight-mediated PDT (DL-PDT) has shown similar efficacy to c-PDT, was nearly painless, and was well tolerated. Overall, DL-PDT effectively treats AK and offers a simpler and better tolerated treatment option than c-PDT. This consensus panel provided recommendations on the use of DL-PDT in Latin America (LATAM) for the treatment of actinic damage associated with few or multiple AKs. The panel was comprised of eight dermatologists from different LATAM countries who have experience using PDT for the treatment of actinic damage. The panel reviewed the relevant literature and provided personal expertise with regard to using DL-PDT for the treatment of photodamage with or without AK. The recommendations formulated by the expert panel provide evidence- based guidelines on all aspects of DL-PDT for the treatment of actinic damage associated with AK in different regions of LATAM. These recommendations provide guidance for dermatologists to ensure maintenance of efficacy and safety of DL-PDT when treating actinic damage, associated with few or multiple AKs in sun-exposed skin.